Push and pull factors influencing domestic visitors to Kilim Karst Geoforest Park, Langkawi - Zameli, Nurul Hikmah; Mohammad Afandi, Syamsul Herman; Samdin, Zaiton; Shuib, Ahmad (Forestry Department Peninsular Malaysia, 2013)
This paper examines the push and pull factors affecting tourists' visit to Kilim Karst Geoforest Park (KKGP), Langkawi. In this study, the push and pull model was applied as the construct for tourists' motivation in choosing a holiday destination. Survey sessions were carried out at KKGP. A total of 300 usable questionnaires were collected. Multiple regression analysis was employed to determine the factors affecting frequency of visit to Kilim which are the tourists' level of education and perception of the park. Findings from this study can assist the authority to manage the development and services according to tourists' need.